Antenatal anaesthesia clinics - the way forward? - Felicity Plaat; Catherine Harris (BMC, 2018)
Abstract Specialist antenatal clinics are increasingly being used to enable anaesthetists to evaluate pregnant women with co-morbidities and those at high risk of obstetric complications. In this journal a team from Israel describe the process of setting up and running such a clinic over a 14 year period. One of the challenges they identify was the limited referral of high risk women. Based on UK and US literature, the use of structured referral tools, clear criteria for referral and regular antenatal multidisciplinary meetings may help to address this.